Comprehensive analysis of transport layers and interface defects in MAPbI3 based PSCs for enhanced efficiency - Mohsen Saadat; Shahla Bameri (Discover Applied Sciences)
Abstract This paper provides a comprehensive optimization of factors that are desired to attaining perovskite solar cells with a high efficiency. The values are showing that a range of the VBM of 5.1—5.5 eV gives the maximum efficiency of 19.80%, while a range of the CBM of 3.4—3.9 eV delivers 21.5%. At the same time, a product of series resistance of 1 Ω·cm2 and shunt resistance of 5000 Ω·cm2 is responsible for efficiencies of 23.16% and 23.25%, respectively. Reducing the number of interface defects from HTL/absorber and ETL/absorber to ≤ 1.0 × 1011 cm−2 and ≤ 1.0 × 1012 cm−2 has a significant effect with highest efficiency of 23.71% and 23.94%. Importantly, Correspondingly, when decreasing further the total defect density to ≤ 1.0 × 1013 cm−3 and adjusting the absorber thickness to ~ 1 μm made them obtain the maximum virtually predicted efficiency of 29.66%. The outcomes of this study provide very important advice on the process of designing and assembly of high-performance perovskite solar cells.